Principals Leadership Competence and Teachers Job Satisfaction in Ondo North Public and Private Secondary Schools - Adepoju Oladehinde Joseph (Inovasi Analisis Data, 2025)
Purpose - This study examines the nexus between principals’ leadership competence and teachers’ job satisfaction in public and private secondary schools in Ondo North Senatorial District, Ondo State, Nigeria. Design/methodology/approach - The study adopted a descriptive survey research design. Data were collected from secondary school teachers using a structured questionnaire that measured demographic characteristics, principals’ leadership competence, and teachers’ job satisfaction. The responses were analyzed using descriptive and inferential statistical procedures to determine patterns and differences across school ownership categories. Findings - Teachers in public and private secondary schools perceived principals’ leadership competence in broadly similar ways. Teachers’ job satisfaction also showed no meaningful difference across school ownership categories. Leadership practices related to motivation, decision-making, communication, fairness, and collegiality emerged as important conditions that support teacher satisfaction, while recognition and career advancement remain areas for improvement. Research limitations/implications - The study was limited to a single senatorial district and relied on self-reported questionnaire data. Future studies should broaden the scope to wider geographic contexts and employ mixed-methods approaches. Practical implications - Education authorities and school proprietors should prioritize leadership development, teacher recognition, professional development, and participatory decision-making in both public and private schools. Originality/value - This study provides contextual evidence that school ownership is less important than leadership quality in shaping teachers’ workplace satisfaction.